Effect of a Lactobacillus Spp-Based Probiotic Culture Product on Broiler Chicks Performance under Commercial Conditions - Vicente, J.L.; Aviña, L.; Torres-Rodriguez, A.; Hargis, B.; Tellez, G. (International Journal of Poultry Science, 2007)
Concern about antimicrobial resistance has led to increased attention to alternatives for controlling infections and increasing performance in animal production. Probiotics and organic acids have gained attention as options in poultry industry. Our laboratory has been working in the selection of lactic acid bacteria, mainly from the genus Lactobacillus, as potential probiotic candidates. Previous data indicates that these selected probiotic bacteria are able to reduce Salmonella infection and improve performance in broiler and turkey under experimental and commercial trials in the USA. The selected probiotic organisms were used in field trials to evaluate their efficacy in commercial conditions in Mexico. In the present report, the probiotic culture significantly reduced mortality (p